2008
DOI: 10.5423/ppj.2008.24.4.392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Delayed Inoculation After Wounding on the Development of Anthracnose Disease Caused by Colletotrichum acutatum on Chili Pepper Fruit

Abstract: Detached chili pepper fruits were inoculated with the conidial suspension of Colletotrichum acutatum JC-24 simultaneously (simultaneous inoculation, SI) and at delayed time (delayed inoculation, DI) after wounding with (delayed wound inoculation, DWI) or without additional wounding (delayed non-wound inoculation, DNI) at the inoculation time. Disease severity was significantly lowered by DNI, compared to SI. By DNI, the disease reduction rates were proportional with the length of delayed time, and greater at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…This study has demonstrated that time after inoculation is a very important factor when comparing the results of several studies. In pear, Spotts et al (1998) found that wound healing decreased the susceptibility of wounds to P. expansum infection after 2 d at 20 • C. Wound response appears to be more efficient in pears than in oranges in providing resistance to a compatible pathogen because only in 2 d they observe similar reductions than those observed in the present study in 4 d. On the other hand, the effect of wound response on resistance of green peppers to Colletotrichum acutatum was even faster because delaying inoculation for only 1 h after wounding resulted in a great reduction in lesion size (Kim et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…This study has demonstrated that time after inoculation is a very important factor when comparing the results of several studies. In pear, Spotts et al (1998) found that wound healing decreased the susceptibility of wounds to P. expansum infection after 2 d at 20 • C. Wound response appears to be more efficient in pears than in oranges in providing resistance to a compatible pathogen because only in 2 d they observe similar reductions than those observed in the present study in 4 d. On the other hand, the effect of wound response on resistance of green peppers to Colletotrichum acutatum was even faster because delaying inoculation for only 1 h after wounding resulted in a great reduction in lesion size (Kim et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…In host plants, wounding stimulates the formation of boundary layers such as the wound periderm and abscission layer as well as the deposition of lignin and suberin into boundary layers; however, these formations are enhanced significantly following inoculation of incompatible hemibiotrophic fungal pathogens ( Kim and Kim, 2002 ; Kim et al, 2004 , 2008 , 2009 ; Rittinger et al, 1987 ). In the current study, the nonhost chili pepper plant had boundary layer formations that were remarkably enhanced following inoculation of the nonhost necrotrophic pathogen Xag 8ra.…”
Section: Discussionmentioning
confidence: 99%
“…The development of different organs and tissue types is governed by the selective expression of distinct fractions of the genome, resulting in the physiologically incompatible differences between the pepper fruit and pepper leaf ( Ma et al, 2005 ). Plant organs that are known to form boundary layers in response to necrotrophic pathogen infections are chili pepper fruit ( Kim et al, 2004 , 2008 ), ginseng root ( Jeon and Kim, 2008 ; Kim et al, 2009 ), cactus stem ( Kim and Kim, 2002 ), and peach bark ( Biggs, 1989 ), all of which are secondarily grown organs in which meristematic cells are regenerated to produce the secondary state of tissues (e.g., periderm) related to the boundary layers (e.g., wound periderm) ( Biggs, 1986 ; Esau, 1977 ). All of these observations suggest that the nonhost defense response of the chili pepper fruit is dynamic and utilizes physiological events in situ that are governed during organ development by the enhanced expression of genes, probably for pathogenesis-related proteins that are required for PCD ( Kim and Hwang, 2015 ) and key enzymes in cell wall-building processes, including lignin formation ( Taheri and Tarighi, 2011 , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conidial concentration was adjusted to 1.0 × 10 6 conidia/ml using a hemacytometer. And then, 1% of carborundum # 400 (Hanawa Chemical Pure, Japan) was added to the conidial suspension for wounding plant surfaces at the spraying time of conidial suspension ( Kim et al, 2008 ). The bacterial isolates were cultured in BHI broth at 28°C for 48 h with shaking at 200 rpm and adjusted to 1.0 × 10 8 cfu/ml.…”
Section: Methodsmentioning
confidence: 99%